The Corellations between Anemia and Chronic Energy Deficiency with the Long of First Stage of Childbirth - Reni Widyastuti Atmoko; Rizky Amelia; Agustin Setianingsih (JURNAL KEBIDANAN, 2021)
Prolonged labor is a prolonged labor time due to delayed progress of labor. Anemia is one of the causes. Chronic Energy Deficiency (CED) also one of the main causes. Based on delivery data from the Kedu Health Center in 2019, it was found that from 832 deliveries, 94 deliveries (69.11%) being prolonged labor both in the first and second stages. The purpose of this study was to determine the effect of anemia and Chronic Lack of Energy on the length of the first stage of labor. The study used an analytic survey study with a cross sectional approach. The population was all pregnant women with an estimated birth from March to April 2021 with a sample of 49 people. The sampling method used accidental sampling. Data analysis using Chi Square test. The results showed that there was a relationship between Chronic Energy Deficiency status in pregnant women and the incidence of prolonged labor (p value = 0.000) and there was a relationship between anemia status and the incidence of prolonged labor (p value = 0.000). The results of this study indicate that there is a relationship between Chronic Energy Deficiency status and anemia status in pregnant women with the incidence of prolonged labor, so midwives need to improve counseling and guidance on nutrition during pregnancy and maintain food intake to avoid poor nutritional status of pregnant women and babies born and inform about the importance of Hb checks and measurements during pregnancy.